Baicalein improves motor dysfunction and cognitive impairment while promoting remyelination in an animal model of multiple sclerosis through the antioxidant mechanism - Wang, Qin; Wang, Ziwen; Li, Yutong; Wang, Qiongzhang; Chen, Yanran; Xu, Benhao; Xu, Haiyun (Frontiers in Pharmacology, 2025)
BackgroundMultiple sclerosis (MS) is a chronic inflammatory and neurodegenerative disease in which repetitive demyelination defeats remyelination and impairs axonal conduction thus resulting in the characteristic disabilities of MS. In searching for new drugs to treat MS, traditional Chinese herbs are gaining increasing attention.MethodsIn animal experiments, an animal model of MS was established by administering cuprizone (CPZ, a copper chelator toxic to cell mitochondria) to C57BL/6J male mice. The therapeutic effects of baicalein (BA) were comprehensively investigated by examining its effects on the CPZ induced neuropathological changes and behavioral abnormalities. Moreover, the cellular and molecular mechanisms underlying the therapeutic effects of BA were explored. The in vitro experiments were done with cultured oligodendrocyte (OL) lineage cells and OLN-93 cell line at various conditions of the absence or presence of CPZ, H2O2, and BA. The viability, development, and mitochondrial function of the cultured cells, as well as oxidative stress measures in the cells were analyzed by means of cell biological and biochemical methods.ResultsIn the in vivo experiments, BA facilitated the recovery of motor and cognitive impairment in CPZ-exposed mice while promoting the remyelination process and inhibiting neuroinflammation in their brains. Underlying these protective effects, BA prevented the nuclear factor erythroid 2-related factor 2 (NRF2) and its downstream antioxidant enzymes (HO-1, NQO1, and SOD2) from over-activation, thereby maintaining the signal pathway in normal levels through its antioxidant actions. The in vitro experiments provided evidence that both CPZ and H2O2 delay the development of oligodendrocyte (OL) lineage cells by damaging mitochondria of the cells and resulting in oxidative stress. BA effectively prevented cultured OLs from development delay by scavenging ROS resulting from damaged mitochondria of the cells.ConclusionThese data demonstrate that BA facilitates remyelination and development of OL lineage cells in the MS model of CPZ-exposed mouse by its antioxidant actions thereby encouraging future clinical applications of BA in treating patients with MS.